Antibacterial activity of seneciolactone isolated from Senecio scandens against some common gastrointestinal tract disease causing bacterial pathogens (Bangladesh Journal of Pharmacology, 2016)
The objective of the present investigation was to study the antibacterial effect of seneciolactone isolated from the methanolic extract of Senecio scandens against five bacterial pathogens which are known to cause several gastrointestinal tract diseases. Disc diffusion assay and agar well diffusion assays were used to examine the antibacterial efficacy of this compound by measuring zones of inhibition and MIC/MBC values. Scanning electron microscopy (SEM) was involved to study the effect of this compound on cellular morphology of Shigella dysenteriae. Results revealed that seneciolactone exhibited moderate to potent antibacterial activity against different bacterial strains. Zones of inhibition and MIC/MBC values indicated that seneciolactone was most potent against S. dysenteriae followed by Pseudomonas aeruginosa and E. coli. SEM results indicated that seneciolactone induced potent damage to the cell membrane of the tested bacteria. As compared to the untreated control which exhibited normal cellular morphology, the seneciolactone treated bacterial cells revealed severe damage to the cellular membrane particularly at the higher doses.